Safety of patients and providers in lung cancer surgery during the COVID-19 pandemic. (5th November 2020) - Chang, Stephanie H; Zervos, Michael; Kent, Amie; Chachoua, Abraham; Bizekis, Costas; Pass, Harvey; Cerfolio, Robert J
Abstract: OBJECTIVES: The coronavirus disease 2019 (COVID-19) pandemic has resulted in patient reluctance to seek care due to fear of contracting the virus, especially in New York City which was the epicentre during the surge. The primary objectives of this study are to evaluate the safety of patients who have undergone pulmonary resection for lung cancer as well as provider safety, using COVID-19 testing, symptoms and early patient outcomes. METHODS: Patients with confirmed or suspected pulmonary malignancy who underwent resection from 13 March to 4 May 2020 were retrospectively reviewed. RESULTS: Between 13 March and 4 May 2020, 2087 COVID-19 patients were admitted, with a median daily census of 299, to one of our Manhattan campuses (80% of hospital capacity). During this time, 21 patients (median age 72 years) out of 45 eligible surgical candidates underwent pulmonary resection—13 lobectomies, 6 segmentectomies and 2 pneumonectomies were performed by the same providers who were caring for COVID-19 patients. None of the patients developed major complications, 5 had minor complications, and the median length of hospital stay was 2 days. No previously COVID-19-negative patient ( n  = 20/21) or healthcare provider ( n  = 9: 3 surgeons, 3 surgical assistants, 3 anaesthesiologists) developed symptoms of or tested positive for COVID-19. CONCLUSIONS: Pulmonary resection for lung cancer is safe in selected patients, even when performed by providers who care for COVID-19 patients in a hospital with a large COVID-19 census. None of our patients or providers developed symptoms of COVID-19 and no patient experienced major morbidity or mortality. Abstract : The global coronavirus disease 2019 (COVID-19) pandemic [1] and the resultant strain on the healthcare system have altered the current practice of medicine and how patients seek care.